2013
DOI: 10.1063/1.4813862
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of traps in InAlN/GaN and AlGaN/GaN high electron mobility transistors using constant drain current deep level transient spectroscopy

Abstract: Traps in InAlN/GaN and AlGaN/GaN high electron mobility transistors (HEMTs) are identified and compared using constant drain-current deep level transient spectroscopy (CID-DLTS). For both structures with different barrier materials, the same drain-access electron trap at EC−0.57 eV dominates the drain-controlled CID-DLTS trap spectrum. This suggests that the physical source of this trap, previously associated with drain-lag, is not present in the barrier but instead is likely to reside in the GaN-buffer. Gate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 25 publications
4
50
0
Order By: Relevance
“…For proton-irradiation at 1.8 MeV, both AlGaN/GaN and AlGaN/AlN/GaN HEMTs showed significant degradation, around 40% drain current reduction, 22,24 after the devices were exposed to protons at a dose of 10 14 cm −2 . Sasikumar et al 71 have identified two main levels as being responsible for the threshold voltage shifts in irradiated AlGaN/GaN HEMTs, namely at E C −0.3.25 eV and at E C −0.1.25 eV. The latter is possibly the nitrogen interstitial defect, while the former is not firmly identified.…”
Section: Changes In Gan-based Hemt Performance After Irradiationmentioning
confidence: 99%
See 3 more Smart Citations
“…For proton-irradiation at 1.8 MeV, both AlGaN/GaN and AlGaN/AlN/GaN HEMTs showed significant degradation, around 40% drain current reduction, 22,24 after the devices were exposed to protons at a dose of 10 14 cm −2 . Sasikumar et al 71 have identified two main levels as being responsible for the threshold voltage shifts in irradiated AlGaN/GaN HEMTs, namely at E C −0.3.25 eV and at E C −0.1.25 eV. The latter is possibly the nitrogen interstitial defect, while the former is not firmly identified.…”
Section: Changes In Gan-based Hemt Performance After Irradiationmentioning
confidence: 99%
“…Similarly, the V Ga defect may be listed as having an energy level of E C −2.5 eV, which is equivalent to the E V +1.0 eV value discussed earlier. 56,57,71 Most of the changes in GaN due to proton or electron damage can be understood in terms of introduction of these primary point defects and for example, the carrier removal rate in GaN for light particles is well accounted for by the introduction of these simple defects. At higher doses or when the GaN contains high levels of dopants or other impurities, complexes involving the primary radiation damage defects and these other impurities can occur and the situation becomes more complicated.…”
Section: Defects In Gan After Irradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The increased density of deeper trap levels increases scattering leading to shorter L. The extended defects generated in the buffer layer can be responsible for changes in dc properties including increases in gate leakage current. 28,35 The effectiveness of annealing for gamma induced defect mitigation has been explored in Ref. 33.…”
mentioning
confidence: 99%